Combining ability of earlymaturing white maize inbreds under stress and nonstress environments - Badu-Apraku, Baffour; Oyekunle, M.; Akinwale, R.O.; Lum, A.F. (Wiley, 2011)
Maize (Zea mays L.) hybrids resistant to Striga hermonthica (Del) Benth and tolerant to drought are vital to the sustainability of productivity of the maize-based farming systems of West and Central Africa (WCA). Thirty-six diallel crosses derived from nine early maturing white maize inbreds were evaluated under drought, well-watered, striga-infested, and striga-free conditions at five locations in Nigeria between 2007 and 2009. The objective was to examine the combining ability, performance and stability of the inbreds, and to identify the heterotic groups. Additive and nonadditive gene actions were important in the control of the inheritance of drought tolerance and striga resistance in the inbreds. General combining ability (GCA) mean squares of grain yield and other traits were larger than those of specific combining ability (SCA), indicating that additive gene action was more important in the inheritance of drought tolerance. The GCA mean squares for striga damage rating at 8 and 10 weeks after planting (WAP) were about six and five times greater than those of the SCA, indicating that additive gene action played a major role in the inheritance of the striga traits. The GGE biplot analysis revealed that TZEI 4 and TZEI 5 were the most promising inbreds in yield performance and stability across the test environments. Two heterotic groups were identified; [TZEI 7, TZEI 19, TZEI 2, TZEI 4] and [TZEI 5, TZEI 3]. Tester TZEI 3 was the closest to the ideal tester. Entry TZEI 7 had the highest GCA effects and TZEI 2 the lowest.